Cultural diversity in Africa: colonial legacy and construction of alternatives: introduction - Sá, Ana Lúcia; Aixelà, Y. (Nordic Journal of African Studies, 2013)
This dossier considers how African cultural diversity was handled during different historical periods and case studies1. The aim is to analyze whether colonization triggered or exacerbated friction in social and cultural coexistence in the contexts under study, whether these tensions remain today and whether these factors are an obstacle to political solutions which are sensitive to the recognition of cultural diversity.